An accurate, high-speed, portable bifunctional electrical detector for COVID-19 - Ke, Guojun; Su, Dingkai; Li, Yu; Zhao, Yu; Wang, Honggang; Liu, Wanjian; Li, Man; Yang, Zhiting; Xiao, Fang; Yuan, Yao; Huang, Fei; Mo, Fanyang; et al. (Science China materials, 2021)
Coronavirus disease 2019 (COVID-19), caused by SARS-CoV-2, has rapidly spread and caused a severe global pandemic. Because no specific drugs are available for COVID-19 and few vaccines are available for SARS-CoV-2, accurate and rapid diagnosis of COVID-19 has been the most crucial measure to control this pandemic. Here, we developed a portable bifunctional electrical detector based on graphene fieldeffect transistors for SARS-CoV-2 through either nucleic acid hybridization or antigen-antibody protein interaction, with ultra-low limits of detection of ~0.1 and ~1 fg mL −1 in phosphate buffer saline, respectively. We validated our method by assessment of RNA extracts from the oropharyngeal swabs of ten COVID-19 patients and eight healthy subjects, and the IgM/IgG antibodies from serum specimens of six COVID-19 patients and three healthy subjects. Here we show that the diagnostic results are in excellent agreement with the findings of polymerase chain reaction-based optical methods; they also exhibit rapid detection speed (~10 min for nucleic acid detection and ~5 min for immunoassay). Therefore, our assay provides an efficient, accurate tool for high-throughput point-of-care testing.